Characterization of the genome of a phylogenetically distinct tospovirus and its interactions with the local lesion-induced host Chenopodium quinoa by whole-transcriptome analyses - Chou, Wan-Chen; Lin, Shih-Shun; Yeh, Shyi-Dong; Li, Siang-Ling; Peng, Ying-Che; Fan, Ya-Hsu; Chen, Tsung-Chi (PLOS ONE, 2017)
Chenopodium quinoa is a natural local lesion host of numerous plant viruses, including tospoviruses (family Bunyaviridae). Groundnut chlorotic fan-spot tospovirus (GCFSV) has been shown to consistently induce local lesions on the leaves of C. quinoa 4 days post-inoculation (dpi). To reveal the whole genome of GCFSV and its interactions with C. quinoa, RNA-seq was performed to determine the transcriptome profiles of C. quinoa leaves. The high-throughput reads from infected C. quinoa leaves were used to identify the whole genome sequence of GCFSV and its single nucleotide polymorphisms. Our results indicated that GCFSV is a phylogenetically distinct tospovirus. Moreover, 27,170 coding and 29,563 non-coding sequences of C. quinoa were identified through de novo assembly, mixing reads from mock and infected samples. Several key genes involved in the modulation of hypersensitive response (HR) were identified. The expression levels of 4,893 deduced complete genes annotated using the Arabidopsis genome indicated that several HR-related orthologues of pathogenesis-related proteins, transcription factors, mitogen-activated protein kinases, and defense proteins were significantly expressed in leaves that formed local lesions. Here, we also provide new insights into the replication progression of a tospovirus and the molecular regulation of the C. quinoa response to virus infection.